A simple constant-current neural stimulator with accurate pulse-amplitude control - De Lima, J. A. [UNESP]; Cordeiro, A. S. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2001)
A simple constant-current electrocutaneous stimulator for high-impedance loads using low-cost, standard high-voltage components is presented. A voltage-regulator powers an oscillator built across the primary of a transformer whose secondary delivers, after rectification, the high-voltage supply to switched current-mirrors in the driving stage. Since the compliance high-voltage is proportional to the stimulation current, overall power consumption is minimized. By adjusting the regulated voltage, control of the pulsed-current amplitude is achieved. A prototype with readily available components features stimulation currents of amplitude and pulsewidth in the range 0≤Iskin≤20mA and 50μs ≤Tpulse≤1ms, respectively. Pulse-repetition spans from 1 Hz to 10Hz. Worst-case ripple is 3.7% @Iskin=1mA. Measured pulse fall-time is shorter than 32μs. Overall consumption is 4.4W @Iskin=20mA. Subject isolation from line is 4KV.